2009
DOI: 10.1128/jvi.00747-09
|View full text |Cite
|
Sign up to set email alerts
|

Role for G-Quadruplex RNA Binding by Epstein-Barr Virus Nuclear Antigen 1 in DNA Replication and Metaphase Chromosome Attachment

Abstract: Latent infection by Epstein-Barr virus (EBV) requires both replication and maintenance of the viral genome. EBV nuclear antigen 1 (EBNA1) is a virus-encoded protein that is critical for the replication and maintenance of the genome during latency in proliferating cells. We have previously demonstrated that EBNA1 recruits the cellular origin recognition complex (ORC) through an RNA-dependent interaction with EBNA1 linking region 1 (LR1) and LR2. We now show that LR1 and LR2 bind to G-rich RNA that is predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
151
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(157 citation statements)
references
References 63 publications
1
151
0
1
Order By: Relevance
“…Recently, we showed that ICP27 binds specifically to GC-rich sequences but that the N-terminal portion of ICP27 encoding the RGG box does not bind Gquartet structures (5). This finding was surprising because the RGG boxes of two other proteins that bind nucleic acids, FMRP and EBNA1, have been shown to bind to G-quadruplex or G-quartet structures (29,30). G quartets are complex tertiary structures that can form readily in DNA or RNA containing three or more consecutive guanines (4,8,30).…”
Section: Discussionmentioning
confidence: 69%
“…Recently, we showed that ICP27 binds specifically to GC-rich sequences but that the N-terminal portion of ICP27 encoding the RGG box does not bind Gquartet structures (5). This finding was surprising because the RGG boxes of two other proteins that bind nucleic acids, FMRP and EBNA1, have been shown to bind to G-quadruplex or G-quartet structures (29,30). G quartets are complex tertiary structures that can form readily in DNA or RNA containing three or more consecutive guanines (4,8,30).…”
Section: Discussionmentioning
confidence: 69%
“…The presence of G-quadruplexes in viral genomes was previously reported (reviewed in reference 67). Interestingly, BRACO-19 negatively affects genome-processing activities, such as replication and transcription of herpes simplex virus 1 (68), Epstein-Barr virus (69), and human immunodeficiency virus type 1 (70). Unlike these viruses, however, in silico analyses of the HHV-6A/B genomes indicate that potential G-quadruplex structures are located exclusively in the viral TMR and not within coding regions (70).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is unclear whether the effect of the G-quadruplex ligand, PDS, solely targets EBNA1-specific G-quadruplexes in vivo. Notably, it is reported that protein domains within EBNA1 bind G-rich RNAs that are predicted to form G-quadruplex structures 46 , suggesting a further level of regulation whereby EBNA1 protein may also selfmodulate its expression using G-quadruplexes as regulatory elements. Modulation of the translational regulatory effects of these G-quadruplexes has the potential to enhance immune recognition of virally infected cells or inhibit replication of the viral genome, leading to elimination of viral latency.…”
Section: Discussionmentioning
confidence: 99%